Reports of atypical shoulder pain and dysfunction following inactivated influenza vaccine, Vaccine Adverse Event Reporting System (VAERS), 2010–2017. Issue 5 (29th January 2020) - Hibbs, Beth F.; Ng, Carmen S.; Museru, Oidda; Moro, Pedro L.; Marquez, Paige; Woo, Emily Jane; Cano, Maria V.; Shimabukuro, Tom T.
Abstract: Background: Vaccines administered into or too close to underlying joint structures have the potential to cause shoulder injuries. Limited data exist on the epidemiology of such events. Objective: To describe case reports of atypical shoulder pain and dysfunction following injection of inactivated influenza vaccine (IIV). Methods: We searched the Vaccine Adverse Event Reporting System (VAERS) database from July 2010 to June 2017 for reports of atypical shoulder pain and dysfunction following IIV. When identifying reports, we made no assumptions about true incident injury or causality with respect to vaccination. Pain had to begin <48 h after vaccination and signs and symptoms had to continue for >7 days to differentiate from self-limited local reactions. We conducted descriptive analysis. Results: We identified 1220 reports that met our case definition (2.0% of all IIV reports, range 1.5%-2.5% across influenza seasons). Median age was 52 years (range 16–94) and most patients (82.6%) were female. Shoulder pain (44.1%), injected limb mobility decreased (40.8%), joint range of motion decreased (21.2%), rotator cuff syndrome (9.2%), and bursitis (9.0%) were frequently reported. In 86.6% of reports, signs and symptoms had not resolved by the time of report submission. In reports that included descriptions suggesting contributing factors (n = 266), vaccination given "too high" on the arm was cited in 81.2%. Nearly half (n = 605, 49.6%) of reports described a healthcare provider evaluation. Treatments included non-narcotic analgesics, physical therapy, and corticosteroid injection. Vaccinations were most commonly administered in a pharmacy or retail store (41.0%) or doctor's office or hospital (31.6%). Conclusions: Reports of atypical shoulder pain and dysfunction following IIV were uncommon, considering the amount of IIV use, and stable across influenza seasons. While specific etiology of cases is unknown, improperly administered vaccine, which is preventable, might be a factor. Prevention strategies include education, training, and adherence to best practices for vaccine administration.